Características de produção e qualidade do leite cru captado por usinas de leite na Zona da Mata de Minas Gerais - Liana Lara Lima (2007)
In 2002, the Brazilian government implemmented the Normative Instruction 51 (IN-51)establishing an important step to improve milk quality in this country. According to thepatterns required by the IN-51, this study was conducted with 183 samples of raw milkcollected from different properties, during the summer of 2006, in the State of MinasGerais, Brazil. The evaluated milk was produced in properties regulated by the stateinspection service and the parameters used were from this national legislation: totalbacterial count, somatic cell count, milk composition (fat, protein, total solids, lactoseand solids non fat), freezing point and qualitative tests for detection of inhibitorysubstances in milk. Questionnaires containing questions about hygienic and productionpractices were filled out during interviews with the producers. It was verified that themain disagreement with the IN-51 patterns was total bacterial count. The conclusion ofthe study is that poor hygienic practices during milking and low level of technicalinformations were the major problem for milk quality